Synthesis, Characteristics and Application of Single Atom Catalysts - Zhao, Shiyong (Curtin University, 2020)
Single-atom catalysts (SACs), comprised of monodispersed metal atoms on various supports with large surface area, have been demonstrated to exhibit high efficiency and selectivity in energy-related or environmental catalysis, far exceeding those of metal nanoparticles catalysts. However, the challenge of SACs is how to develop a facile method for the controllable synthesis of SACs with high mass loading. Therefore, a series of works was conducted around the controlled synthesis, characterization and application of SACs